Pelatihan Keterampilan Kompetensi Interpersonal untuk Meningkatkan Kepercayaan Diri Penggiat Anti Narkoba - Herny Novianti (UIN Siber Syekh Nurjati Cirebon, 2022)
This study aims to produce interpersonal competency skills training to increase the confidence of anti-drug activists in the business and private world. The design that will be carried out in this study is a pre-experimental design with one group pretest-posttest design. Data collection uses a self-confidence instrument which includes aspects of belief in self-ability, optimism, objective, responsibility, and rationale. The sample in this study were anti-drug activists in the business and private world of BNN Cirebon City in 2022, aged 25-40 years, totaling 50. The results showed that interpersonal competency skills training was effective for increasing the confidence of anti-drug activists, as evidenced by an increase in score of 4 aspects, namely: self-confidence, optimistic, responsible, and rational, while the insignificant aspect is objective. Recommendations for this research are addressed to various parties including guidance and counseling study programs, anti-drug activists, addiction counseling practitioners, and further research.